Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21037/jtd.2018.03.123
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic analysis in T2W and SPAIR T2W MRI: predict treatment response to chemoradiotherapy in esophageal squamous cell carcinoma

Abstract: Radiomic analysis based on pretreatment T2W- and SPAIR T2W-MRI can be served as imaging biomarkers to predict treatment response to CRT in ESCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…In particular, the GLCM correlation, the Gray‐Level Non‐Uniformity calculated from GLSZM, GLDM and GLRLM, the GLDM Dependence Non‐Uniformity, the GLRLM Run‐Length Non‐Uniformity and the NGTDM Coarseness are common in both studies. Some of these features have been also reported as predictive of treatment response in esophageal cancer, able in differentiating prostate cancer aggressiveness or able in characterizing structural modifications induced by RT in normal tissues . Other studies focused on the reproducibility of T2w‐MRI radiomic features in the prostate using different scanners, and, among the considered features families, GLCM was the most reproducible and with higher ability in discriminating tumor and nontumor regions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the GLCM correlation, the Gray‐Level Non‐Uniformity calculated from GLSZM, GLDM and GLRLM, the GLDM Dependence Non‐Uniformity, the GLRLM Run‐Length Non‐Uniformity and the NGTDM Coarseness are common in both studies. Some of these features have been also reported as predictive of treatment response in esophageal cancer, able in differentiating prostate cancer aggressiveness or able in characterizing structural modifications induced by RT in normal tissues . Other studies focused on the reproducibility of T2w‐MRI radiomic features in the prostate using different scanners, and, among the considered features families, GLCM was the most reproducible and with higher ability in discriminating tumor and nontumor regions.…”
Section: Discussionmentioning
confidence: 99%
“…Performance of various methods to construct predictive models was analyzed [20,21,[26][27][28][29]. Zhang et al observed that the combination of clinical, conventional PET and radiomic PET features in a support vector machine (SVM) model achieved highest accuracy in predicting complete pathologic response, while Ypsilantis et al showed that a convolutional neural network (CNN) outperformed machine learning classifiers, including SVM, logistic regression model (LR), random forest (RF), and gradient boosting [21,28].…”
Section: Esophageal Cancermentioning
confidence: 99%
“…MRI has multiparametric imaging ability and can provide more valuable data for radiomics than monomodality imaging methods such as computed tomography (CT) by high-throughput extraction of quantitative image features ( 12 ). Texture features derived from MRI images have been proven to be helpful in assessing tumors ( 13 15 ). Previous studies indicated that texture features show potential for distinguishing benign from malignant lesions for breast cancer ( 16 ).…”
Section: Introductionmentioning
confidence: 99%